2021
DOI: 10.1097/qad.0000000000002902
|View full text |Cite
|
Sign up to set email alerts
|

Etravirine in treatment-experienced HIV-1-infected children 1 year to less than 6 years of age

Abstract: Objective: To describe the pharmacokinetics, safety, and efficacy of etravirine (ETR) in HIV-infected children 1 to less than 6 years of age. Design: Phase I/II, open-label, multicenter, dose-finding study. Methods: Antiretroviral therapy (ART)-experienced children in two age cohorts (I: 2 to <6 years; II: 1 to less than 2 years) received weight-based ETR, swallowed whole or dispersed in liquid, with optimized ART including a ritonavir-boosted pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…A Spanish observational cohort ( N =23) of treatment-experienced children/adolescents reported similar findings; 78% had VL<50 copies/mL at a median of 48 weeks [ 10 ]. The recent P1090 trial on ETR in treatment-experienced children aged 1–6 years reported that among children on the final dose, 75% of those aged 2–6 years and 33.3% of those aged 1–2 years had VL<400 copies or ≥2 log reduction from baseline at week 48 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spanish observational cohort ( N =23) of treatment-experienced children/adolescents reported similar findings; 78% had VL<50 copies/mL at a median of 48 weeks [ 10 ]. The recent P1090 trial on ETR in treatment-experienced children aged 1–6 years reported that among children on the final dose, 75% of those aged 2–6 years and 33.3% of those aged 1–2 years had VL<400 copies or ≥2 log reduction from baseline at week 48 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcome data for ETR in treatment-experienced children and adolescents are limited to single-arm trials and observational studies with <50 patients. These reported 33%-78% viral suppression <50 copies/mL at 48 weeks [9][10][11][12][13][14]. Common adverse reactions included gastrointestinal disorders and rashes.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent Phase I/II multicenter study including 26 children (46.2% girls) aged 1 year to < 6 years from South Africa, Brazil, and the United States, approximately 20% experienced adverse effects which included rash, cough, nasal congestion, rhinorrhea, pharyngitis, diarrhea, and vomiting. Two children experienced elevated lipase levels, which is a rare adverse effect of ETR use, and resulted in one leaving the study ( MacBrayne et al, 2021 ) [M]. Another study aimed to determine the long-term effects of ETR on the reproductive system, liver, kidneys, and bones in mature 8-week-old male Wistar rats.…”
Section: Drugs Active Against Human Immunodeficiency Virus (Hiv): Non...mentioning
confidence: 99%
“…Этравирин (ETR) -ненуклеоиздный ингибитор обратной транскриптазы второго поколения, эффективность и безопасность применения которого при лечении ВИЧ-инфицированных детей от года до шести лет продемонстрировали недавние зарубежные исследования [38]. Учитывая, что список препаратов, разрешенных для лечения ВИЧинфицированных детей младшего возраста, крайне ограничен, применение этравирина для лечения ВИЧ-инфекции у детей в будущем представляется перспективным [39].…”
unclassified